Cartoon Illustration as an Effective Medium of Expression in Nigerian Press - Josiah Okeke (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2025)
Several avenues have been explored by man to express opinions and make them accessible for public appraisals. Sometimes, there are occasions where it is not very safe and prudent for opinions to be expressed directly for security reasons. Cartoon therefore, becomes very eloquent but subtle here, especially in communicating political and social issues. Volumes of literacy language are effective means of communication, but sometimes they sound boring to the beholder, who may have to go through all the lines and pages of a text before the message is comprehended. On the contrary, a small cartoon is capable of speaking volumes to the beholder at a mere glance. The study therefore, presents cartoon as a viable and easy means of delivering messages to the beholder in view of its visual attributes. It specifically focuses on examining the humours and satires inherent in cartoons and their implied meanings, which majorly circumscribe on denouncing the societal vices. The cartoons that constitute the subject matter of the discourse are culled from various sources, all of which feature as mouthpieces against the evil practices pertinent to the Nigerian politicians.